ETIKA MASYARAKAT MADURA DALAM TRADISI TANEAN LANJHANG - Salamet A (UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2019)
TheTanean Lanjhangtradition is a reflection of the life of the Maduresepeople.Tanean Lanjhangby itself will shape the lifestyle ofthe Madurese peoplefrom generation to generation, because the values taught in the life of the TaneanLanjhangtraditioncontinuetotransformtothenextgenerationasthevalueofmo-rality. Thus, this article will describe the ethics of theMadurese community basedon implied values and philosophies or proverbs in the Tanean Lanjhang traditionwhich are still taught in the life of the Madurese people.The ethics referred to inthis discussion are descriptive ethics which only describe moral behavior in abroad sense. Descriptive ethics is only describing and does not provide an assess-ment of whether a certain behavior can be accepted or should be rejected. This de-scriptive ethics discussion of the Tanean Lanjhang tradition will by itself describethe personality or identity of the Madurese people.